STRATEGI PENGUATAN MINAT GENERASI MUDA TERHADAP KESENIAN TRADISIONAL MELALUI OPTIMALISASI PROMOSI DAN EDUKASI UNTUK MENDUKUNG REGENERASI SENIMAN - Surakhman (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
The significant decline in youth interest toward traditional arts in Cirebon City, reflected in the minimal regeneration of artists and stagnation of art studio activities, highlights the urgent need for strategic policies to preserve local culture. This policy paper aims to formulate a strategy to strengthen youth interest in traditional arts through the optimization of relevant and sustainable promotion and education. Using a qualitative-descriptive method based on literature review and secondary data from local government reports, academic journals, and observations of art communities, the analysis is grounded in Bourdieu’s theory of habitus and Rogers’ diffusion of innovation. Data collection involved documentation of regulations, program evaluations, and case study reviews. Thematic analysis and policy scoring using Bardach and Dunn’s models were applied to identify the most viable policy option. The findings indicate that optimizing cultural education is the most appropriate strategy, fulfilling criteria of effectiveness, efficiency, feasibility, and contextual relevance. The resulting benefits are expected to foster a healthy and adaptive ecosystem for artist regeneration, while encouraging greater youth participation in the preservation of traditional arts. Recommendations include integrating traditional arts into the formal education curriculum, training educators, digitalizing cultural learning materials, and strengthening the "Art Studio in Schools" program in a structured and sustainable manner.